CHEMICAL AND MINERALOGICAL PROPERTIES OF ULTISOLS OF SASAMBA AREA, EAST KALIMANTAN - Prasetyo, B.H.; Suharta, N.; H., Subagyo; ., Hikmatullah (Indonesian Journal of Agricultural Science, 2001)
Ultisols are a major group of marginal soils extensively found in the upland area of Indonesia. To better understand the potential of the Ultisols developed from claystone and sandstone in the Sasamba Integrated Economical Development Area in East Kalimantan, chemical and mineralogical characteristics of 27 Ultisols pedons consisting of 76 topsoil and 118 subsoil samples were investigated. Besides analysis and interpretation of data, relationships of several soil characteristics wereconstructed using simple regression. The results indicated that Ultisols showed acid to very acid reaction, had low content of organic matter and low base saturation. Soils generally exhibited net negative charge, and the point of zero charge was reached at pH 3.6. Both potential and available phosphates were low, and there was a trend that amorphous aluminum was responsible for phosphate fixation. The low content of exchangeable potassium in topsoil and subsoil indicated a positive correlation with potential potassium. Clay mineral was composed chiefly of kaolinite, with small amounts of illite, vermiculite, and quartz. The domination of kaolinite and low organic matter content causes the soils to have low cation exchange capacity. Soil management in this area should befocused on building up and maintaining soil fertility, and applying appropriate soil conservation techniques to minimize erosion. To obtain sustained productivity, various soil amendments including the use of farm and/or green manure, liming with agricultural lime, and application of rock phosphate and K fertilizers were highly recommended.